Inisiasi Pembentukan Agen “SARAS” (Sa Tra Miras) di Asrama Mahasiswa Mamberamo Raya - Violita, Fajrin (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: The high rate of alcohol consumption among teenagers not only poses a risk for disease but also triggers deviant behaviors such as violence, traffic accidents, and risky sexual behavior. Alcohol consumption can also negatively affect the learning process due to decreased concentration. The purpose of this community service activity is to encourage the formation of “SARAS” (Sa Tra Miras) Agents who will act as continuous education providers and raise awareness about the negative impacts of alcoholic beverages in the Mamberamo Raya Student Dormitory. Methods: This community service was carried out in partnership with the Mamberamo Raya Student Dormitory management. The method was brainstorming, supported by poster media. A pre- and post-test questionnaire is used to assess the impact of the activity. Results: The initiation of